Tropical ecolodge design manual - Glenski, Andrew J. (Kansas State University, 2010)
The International Ecotourism Society (TIES), the world’s first ecotourism organization, coined what has become the most succinct definition of ecotourism: “Responsible travel to natural areas that conserves the environment and improves the wellbeing of local people (Honey 2008, p. 6).” Ecolodges are accommodation facilities within ecotourism destinations which must satisfy specific principles, while reflecting the definition of ecotourism. Ecolodge principles include water conservation, preservation of flora and fauna, design to create a small footprint, and interpretive programs to educate both employees and tourists about the surrounding natural and cultural environments, to name just a few. (Mehta 2002, p. 5) Tropical locations, where ecolodges are often found, are comprised of unique ecosystems. With tropical locales, there are specific considerations that could determine the success of a proposed ecolodge development. As a designer, one must understand the biophysical characteristics on site, to inform design decisions of the ecolodge development. In addition, a designer must understand how the indigenous populations utilize the site culturally, physically and spiritually to fully understand the importance of the ecolodge development. (Mehta 2002, p. 12) When proper analysis of cultural and biophysical factors is completed, an ecolodge development is able to conform to the ecotourism definition and satisfy ecolodge principles. Within this manual, a hierarchical list of design principles, guidelines and criteria are communicated to achieve an overall design goal called fitness design. A “fit” design is intended to achieve sustainability and quality of life for the environment and the communities that have daily interaction with the development. As readers navigate through the document, they will be exposed to various considerations of a tropical ecolodge development. The intent of the manual is to provide a structural framework to guide an ecolodge design process.
Keywords: Ecolodge design; Tropical ecosystems; Fitness design; Ecotourism; Design principles; Landscape Architecture (0390)